Data entry - Humphrey, Doris D. (Thomson/South-Western, 2005)
This text and software package is designed to develop speed and accuracy in entering alphabetic and numeric data using the keypad and top row. Users must already know the alphanumeric keys, but the software will develop job-entry skills. The software measures keystroke speed and accuracy on both straight copy and business forms comparable to those used in the workplace. The dedicated software also includes a Training Center for extensive skill practice and four projects to familiarize users with the skills needed in industry specific data entry careers. These industries are insurance, retail, hotel and medical